Determining Self-Efficacy and Its Related Factors in Adolescents with Major β-Thalassemia Referring to Selected Hospital in Tehran - Khalaf Saad, Marwah; Javaheri Tehrani, Fereshteh; Shariatpanahi, Shabnam; Abedini, Zahra; Nasiri, Maliheh (Advances in Nursing & Midwifery, 2022)
Abstract Introduction: Major β-Thalassemia is one of the most common hereditary anemias in the world and is a health problem associated with the absence or reduction of globin chain production. Self-efficacy helps adolescents with chronic illness to strength their ability to handle the routine tasks and to achieve treatment goals. Because of the importance Major β-Thalassemia in adolescents and its effects on their quality of life, we decided to do this study with the aim of “Determining self-efficacy and its related factors in adolescents Major β-Thalassemia referring to selected hospital in Tehran”. Methods: The present study used a descriptive comparative cross-sectional design on 100 adolescents with Major β-Thalassemia referring to Shohadaye Tajrish hospital in Tehran in 2022. We used a census design to collect data in a fixed duration and in three work shifts in the morning, evening and night in the relevant units. The data collection tools included of demographic and Self-Efficacy Questionnaire for Children (SEQ-C). The collected data were analysed by SPSS Software version 20 via statistical tests included of Pearson or Spearman coefficient, t test and ANOVA test. Results: The average age of the participant adolescents were 15.40 ± 2.22. The results of the study showed that the mean score of academic, social and emotional self-efficacy were 26.17±3.91, 24.83±5.33 and 24.49±4.75 respectively. The score of self-efficacy of the participants were approximately in the average range in the three dimensions of the SEQ-C. However, the score of academic self-efficacy was slightly higher than the average range. There are not any significant relationships between the demographic variables and any dimensions of self-efficacy (P-value>0.05). However, the results of T-Test showed significant relationships between the social self-efficacy score and positive history of splenectomy (P-value=0.018). Conclusions: Based on the results of the study, the self-efficacy score of participants in this study were approximately in the average range, therefore, these results showed that, health staffs such as nurses should promote the self-efficacy of adolescents with Major β-Thalassemia through health education.